Antifibrotic effects and mechanisms of mesenchymal stem cell-derived exosomes in a systemic sclerosis mouse model: Possible contribution of miR-196b-5p. Issue 1 (October 2021) - Baral, Hritu; Uchiyama, Akihiko; Yokoyama, Yoko; Sekiguchi, Akiko; Yamazaki, Sahori; Amalia, Syahla Nisaa; Inoue, Yuta; Ogino, Sachiko; Torii, Ryoko; Hosoi, Mari; Matsuzaki, Toshiyuki; Motegi, Sei-ichiro
Highlights: MSCs-derived exosomes suppressed bleomycin-induced dermal fibrosis in mice. MSCs-derived exosome treatment decreased Type I Collagen expression in fibroblasts. miR-196b-5p was most highly expressed in miRNA in MSCs-derived exosomes. miR-196b-5p attenuated TGF-β-induced increased expression of COL1A2 in fibroblasts. Abstract: Background: Systemic sclerosis (SSc) is a connective tissue disorder characterized by the development of fibrosis in the skin and internal organs. Increasing evidence suggests that mesenchymal stem cells (MSCs) can be used to a treatment for fibrotic diseases. Recent studies have demonstrated that some of the biological effects of MSCs are due to the secretion of exosomes. However, the precise mechanisms underlying MSCs-derived exosomes in skin fibrosis are not well understood. Objective: We aimed to elucidate the effect of MSCs-derived exosomes on skin fibrosis in SSc and the mechanism underlying their inhibitory action on fibrosis. Methods: Exosome was collected from MSCs by ultracentrifugation method. We examined the suppressive effect of MSCs-derived exosome on skin fibrosis in bleomycin-induced SSc mouse model. Skin samples from the injected site were collected for further examination, and micro-RNA analysis of MSCs-derived exosome was performed. Results: Injection of MSCs-derived exosomes significantly inhibited bleomycin-induced dermal fibrosis in mice. MSCs-derived exosomes significantly reduced the amount of collagen and the number of α-SMA + myofibroblasts and CD68 + macrophages in lesional skin. They also reduced the expression of type I collagen and TGF-β receptor 1 in fibroblasts in vitro . Moreover, micro-RNA analysis revealed that several microRNAs in MSCs-derived exosomes have antifibrotic potential. We confirmed that overexpression of miR-196b-5p in fibroblasts significantly suppressed collagen type I alpha 2 expression. Conclusion: This study demonstrated that inhibition of collagen type I expression by miR-196b-5p in exosomes might be one of the mechanisms by which MSCs suppress skin fibrosis in an SSc mouse model.